2014
DOI: 10.1007/s11892-014-0548-3
|View full text |Cite
|
Sign up to set email alerts
|

Beyond HbA1c and Glucose: the Role of Nontraditional Glycemic Markers in Diabetes Diagnosis, Prognosis, and Management

Abstract: Fasting glucose and hemoglobin A1c (HbA1c) are the standard measures for diagnosis and monitoring of diabetes. There has been recent interest in nontraditional markers of hyperglycemia, including fructosamine, glycated albumin and 1,5-anhydroglucitol (1,5-AG), as alternatives or adjuncts to standard measures. There is a growing literature linking these nontraditional markers with microvascular and macrovascular complications. Fructosamine and glycated albumin have also been shown to improve identification of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
106
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 100 publications
8
106
0
5
Order By: Relevance
“…Furthermore, the comparison of risk factor associations for elevations in non-traditional versus traditional biomarkers of hyperglycemia is important for the interpretation of these biomarkers in the general population and the clinic. Previous studies have demonstrated strong associations between fructosamine and glycated albumin with microvascular conditions 1, 25, 26 , with associations of similar magnitude to those observed for HbA1c. Data on risk associations using modern assays of fructosamine and glycated albumin with cardiovascular disease are sparse; and previous studies have been limited by cross-sectional designs or prospective studies with small numbers of cardiovascular events 25, 26 .…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, the comparison of risk factor associations for elevations in non-traditional versus traditional biomarkers of hyperglycemia is important for the interpretation of these biomarkers in the general population and the clinic. Previous studies have demonstrated strong associations between fructosamine and glycated albumin with microvascular conditions 1, 25, 26 , with associations of similar magnitude to those observed for HbA1c. Data on risk associations using modern assays of fructosamine and glycated albumin with cardiovascular disease are sparse; and previous studies have been limited by cross-sectional designs or prospective studies with small numbers of cardiovascular events 25, 26 .…”
Section: Discussionsupporting
confidence: 59%
“…4 5 25-27 There is growing evidence that these intermediate-term markers of glycemia are more meaningful indicators of risk for diabetes, cardiovascular disease, and mortality than single glucose measurements 7 8 24 28 by representing the aggregate effects of both fasting glucose and postprandial glucose excursions. 29 GI is a measure of carbohydrate 'quality', based on the rate of glucose released into circulation after consumption of a fixed amount of carbohydrates. It is typically determined by comparing the area of the glucose curve following the consumption of 50 g of a carbohydrate food relative to a referent 50 g food such as white bread or glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylated hemoglobin can accurately reflect the long-term blood glucose control of diabetic and is an important indicator for the condition of diabetes [7][8] . Glycosylated hemoglobin helps people understand diabetes complications and guide patients to control blood glucose [9][10][11] . In 2010, the American Diabetes Association (ADA) suggested that all diabetics should make at least two regular glycosylated hemoglobin tests every year…”
Section: Introductionmentioning
confidence: 99%